DIAGNOSIS AND PREVENTION OF PREECLAMPSIA USING ULTRASOUND DOPPLER STUDIES AND HEMOSTASIS PARAMETERS - Нарт Фарук Кунешко; Михаил Игоревич Кузнецов; Яна Валентиновна Антимонова (The Publishing House Medicine and Enlightenment, 2018)
The aim of the research - early diagnosis and prevention of preeclampsia using ultrasound doppler studnd hemostasis parameters, including hereditary thrombophilia and antiphospholipid antibodies. Materials and methods. All women were examined by doppler sonography. The forms of the blood flow velocity signal were recorded according to the indications of uterine, umbilical, basilar and vertebral arteries of the fetus. The study of hemostasis included the assessment of levels of clotting of blood plasma and parameters of fibrinolysis (íÄí, D-dimer), determination of circulating antiphospholipid antibodies (APA) and genetic forms of thrombophilia. Results. The research included 76 pregnant women. Thrombophilia was found in 31 (63.3 %) pregnant women with complications of pregnancy. Genetic forms (55.1 %) and circulation of antiphospholipid antibodies (22.4 %) were most often observed in patients with and preeclampsia. Tight-placental circulation was abnormal in 21 cases (61,8 %) of pregnancy with delay of intrauterine fetus growth, in 50 % with preeclampsia and in 83,3 % without preeclampsia. Among women with preeclampsia without delay of intrauterine fetus growth, there were 6 cases (40 %) of abnormal uterine-placental hemodynamics. Changes in blood plasma clotting levels and vibroanalysis parameters were most pronounced in cases of pregnancy with abnormal fetal-placental circulation compared to the control group. Conclusion. The widespread use of dopplersonography and thrombophilia study can contribute to the early diagnosis of pregnancy complications suchas preeclampsia and delay of intrauterine fetus growth.